Identification of CACNA1D variants associated with sinoatrial node dysfunction and deafness in additional Pakistani families reveals a clinical significance. - Liaqat, Khurram; Schrauwen, Isabelle; Raza, Syed Irfan; Lee, Kwanghyuk; Hussain, Shabir; Chakchouk, Imen; Nasir, Abdul; Acharya, Anushree; Abbe, Izoduwa; Umair, Muhammad; Ansar, Muhammad; Ullah, Irfan; et al. (J Hum Genet, 2019)
Sinoatrial node dysfunction and deafness (SANDD) syndrome is rare and characterized by a low heart beat and severe-to-profound deafness. Additional features include fatigue, dizziness, and episodic syncope. The sinoatrial node (SAN) drives heart automaticity and continuously regulates heart rate. The CACNA1D gene encoding the Ca1.3 protein expressed in inner hair cells, atria and SAN, induces loss-of-function in channel activity and underlies SANDD. To date, only one variant c.1208_1209insGGG:p.(G403_V404insG) has been reported for SANDD syndrome. We studied five Pakistani families with SANDD and characterized a new missense variant p.(A376V) in CACNA1D in one family, and further characterized the founder variant p.(G403_V404insG) in four additional pedigrees. We show that affected individuals in the four families which segregate p.(G403_V404insG) share a 1.03 MB haplotype on 3p21.1 suggesting they share a common distant ancestor. In conclusion, we identified new and known variants in CACNA1D in five Pakistani families with SANDD. This study is of clinical importance as the CACNA1D founder variant is only observed in families from the Khyber Pakhtunkhwa (KPK) province, in Pakistan. Therefore, screening patients with congenital deafness for SAN dysfunction in this province could ensure adequate follow-up and prevent cardiac failure associated with SAN.
Keywords: Adolescent; Calcium Channels, L-Type; Deafness; Female; Heart Diseases; Humans; Male; Mutation; Pakistan; Pedigree; Prognosis; Sinoatrial Node

Novel digenic inheritance of PCDH15 and USH1G underlies profound non-syndromic hearing impairment. - Schrauwen, Isabelle; Chakchouk, Imen; Acharya, Anushree; Liaqat, Khurram; Nickerson, Deborah A; Bamshad, Michael J; Shah, Khadim; Ahmad, Wasim; Leal, Suzanne M (BMC Med Genet, 2018)
BACKGROUND: Digenic inheritance is the simplest model of oligenic disease. It can be observed when there is a strong epistatic interaction between two loci. For both syndromic and non-syndromic hearing impairment, several forms of digenic inheritance have been reported. METHODS: We performed exome sequencing in a Pakistani family with profound non-syndromic hereditary hearing impairment to identify the genetic cause of disease. RESULTS: We found that this family displays digenic inheritance for two trans heterozygous missense mutations, one in PCDH15 [p.(Arg1034His)] and another in USH1G [p.(Asp365Asn)]. Both of these genes are known to cause autosomal recessive non-syndromic hearing impairment and Usher syndrome. The protein products of PCDH15 and USH1G function together at the stereocilia tips in the hair cells and are necessary for proper mechanotransduction. Epistasis between Pcdh15 and Ush1G has been previously reported in digenic heterozygous mice. The digenic mice displayed a significant decrease in hearing compared to age-matched heterozygous animals. Until now no human examples have been reported. CONCLUSIONS: The discovery of novel digenic inheritance mechanisms in hereditary hearing impairment will aid in understanding the interaction between defective proteins and further define inner ear function and its interactome.
Keywords: Adult; Animals; Cadherins; Hearing Loss; Heterozygote; Humans; Male; Mechanotransduction, Cellular; Multifactorial Inheritance; Mutation; Nerve Tissue Proteins; Pakistan; Pedigree; Usher Syndromes; Young Adult

Sequence variants in nine different genes underlying rare skin disorders in 10 consanguineous families. - Shah, Khadim; Mehmood, Sabba; Jan, Abid; Abbe, Izoduwa; Hussain Ali, Raja; Khan, Anwar; Chishti, Muhammad S; Lee, Kwanghyuk; Ahmad, Farooq; Ansar, Muhammad; Shahzad, Shaheen; Nickerson, Deborah A; et al. (Int J Dermatol, 2017)
BACKGROUND: Genodermatoses represent genetic anomalies of skin tissues including hair follicles, sebaceous glands, eccrine glands, nails, and teeth. Ten consanguineous families segregating various genodermatosis phenotypes were investigated in the present study. METHODS: Homozygosity mapping, exome, and Sanger sequencing were employed to search for the disease-causing variants in the 10 families. RESULTS: Exome sequencing identified seven homozygous sequence variants in different families, including: c.27delT in FERMT1; c.836delA in ABHD5; c.2453C>T in ERCC5; c.5314C>T in COL7A1; c.1630C>T in ALOXE3; c.502C>T in PPOX; and c.10G>T in ALDH3A2. Sanger sequencing revealed three homozygous variants: c.1718 + 2A>G in FERMT1; c.10459A>T in FLG; and c.92delT in the KRT14 genes as the underlying genetic cause of skin phenotypes. CONCLUSION: This study supports the use of exome sequencing as a powerful, efficient tool for identifying genes that underlie rare monogenic skin disorders.
Keywords: 1-Acylglycerol-3-Phosphate O-Acyltransferase; Aldehyde Oxidoreductases; Blister; Collagen Type VII; Consanguinity; DNA Mutational Analysis; DNA-Binding Proteins; Endonucleases; Epidermolysis Bullosa; Epidermolysis Bullosa Dystrophica; Epidermolysis Bullosa Simplex; Exome; Female; Flavoproteins; Homozygote; Humans; Ichthyosiform Erythroderma, Congenital; Ichthyosis Vulgaris; Ichthyosis, Lamellar; INDEL Mutation; Intermediate Filament Proteins; Keratin-14; Lipid Metabolism, Inborn Errors; Lipoxygenase; Male; Membrane Proteins; Mitochondrial Proteins; Muscular Diseases; Neoplasm Proteins; Nuclear Proteins; Pedigree; Periodontal Diseases; Phenotype; Photosensitivity Disorders; Porphyria, Variegate; Protoporphyrinogen Oxidase; Rare Diseases; Sjogren-Larsson Syndrome; Skin Diseases, Genetic; Transcription Factors; Xeroderma Pigmentosum

Mitral regurgitation as a phenotypic manifestation of nonphotosensitive trichothiodystrophy due to a splice variant in MPLKIP. - Shah, Khadim; Ali, Raja Hussain; Ansar, Muhammad; Lee, Kwanghyuk; Chishti, Muhammad Salman; Abbe, Izoduwa; Li, Biao; Smith, Joshua D; Nickerson, Deborah A; Shendure, Jay; Coucke, Paul J; Steyaert, Wouter; et al. (BMC Med Genet, 2016)
BACKGROUND: Nonphotosensitive trichothiodystrophy (TTDN) is a rare autosomal recessive disorder of neuroectodermal origin. The condition is marked by hair abnormalities, intellectual impairment, nail dystrophies and susceptibility to infections but with no UV sensitivity. METHODS: We identified three consanguineous Pakistani families with varied TTDN features and used homozygosity mapping, linkage analysis, and Sanger and exome sequencing in order to identify pathogenic variants. Haplotype analysis was performed and haplotype age estimated. A splicing assay was used to validate the effect of the MPLKIP splice variant on expression. RESULTS: Affected individuals from all families exhibit several TTDN features along with a heart-specific feature, i.e. mitral regurgitation. Exome sequencing in the probands from families ED168 and ED241 identified a homozygous splice mutation c.339 + 1G > A within MPLKIP. The same splice variant co-segregates with TTDN in a third family ED210. The MPLKIP splice variant was not found in public databases, e.g. the Exome Aggregation Consortium, and in unrelated Pakistani controls. Functional analysis of the splice variant confirmed intron retention, which leads to protein truncation and loss of a phosphorylation site. Haplotype analysis identified a 585.1-kb haplotype which includes the MPLKIP variant, supporting the existence of a founder haplotype that is estimated to be 25,900 years old. CONCLUSION: This study extends the allelic and phenotypic spectra of MPLKIP-related TTDN, to include a splice variant that causes cardiomyopathy as part of the TTDN phenotype.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Adult; Alleles; Asian Continental Ancestry Group; Child; Cloning, Molecular; Exome; Female; Genetic Linkage; Haplotypes; HEK293 Cells; Homozygote; Humans; Introns; Male; Mitral Valve Insufficiency; Pakistan; Pedigree; Phenotype; Polymorphism, Single Nucleotide; RNA Splicing; Sequence Analysis, DNA; Trichothiodystrophy Syndromes; Young Adult